The Impact of Short-Term Mega Sporting Event Experiences on Student Learning - Buenano, Andrea L.; Warner, Stacy; Moore, E. Whitney G. (Sport Management Education Journal, 2024)
Short-term mega sporting events provide an opportunity for students to not only gain a memorable career experience but also enhance student skills and learning. However, very few (if any) researchers have explored students’ confidence related to key skills before and after such an event. Thus, the purpose of this study was to assess the effect of experiential learning at the National Football League’s 2023 Super Bowl LVII mega event on students’ learning outcomes. Students (N = 103) responded to an online survey distributed to assess their self-confidence across 18 learning-outcome skills covering problem solving, communication, sport-industry knowledge, and professional development. Each dependent-sample t test done to examine the students’ self-confidence with the individual learning outcome skills was significant (p < .001) and had meaningfully increased (Cohen’s d range: 0.47–0.97) from pre- to postevent. The results suggest that students can experience a notable increase in self-confidence when volunteering at a short-term mega sporting event. From a practical standpoint, the results provide sport management educators with strong evidence of the meaningful student learning related to problem solving, communication, sport-industry knowledge, and professional development that can occur with a single short-term mega-event experience.
Keywords: Experiential Learning; Learning Outcomes; Hands-on Learning; Field Experience; Mega Events; Sporting Events